Selectivity of content and language integrated learning programmes in German secondary schools. Issue 1 (2nd January 2018) - Dallinger, Sara; Jonkmann, Kathrin; Hollm, Jan
ABSTRACT: Despite its increasing popularity and adoption across Europe, Content and Language Integrated Learning (CLIL) is not without its critics. It has been argued that CLIL programmes are highly selective, that is, the students possess more favourable learning prerequisites than their monolingually taught peers. The present study contributes to this debate by investigating possible differences in learning prerequisites between CLIL and non-CLIL students in German CLIL secondary schools. We assessed figural and verbal cognitive skills, family background (immigration background, parents' education, socio-economic status, and cultural capital), and achievement and motivation in the soon-to-be bilingually taught content subject History and in the foreign language of 1362 CLIL and non-CLIL eighth graders. Results indicated significant advantages of CLIL students regarding their verbal cognitive skills, parents' education, socio-economic status, cultural capital, and achievement and motivation in History and in the foreign language. Additionally, it was investigated whether differences in students' foreign language performance would diminish after possible differences in learning prerequisites were taken into account. Multiple regression analyses showed distinct selection effects but CLIL students still outperformed their monolingually taught peers by one to almost two school years (listening comprehension resp. C-test). These results can lay the foundation for an evaluation of the effectiveness of CLIL programmes.